Evaluation and clinical activity test of various concentrations of peel-off gel mask of robusta coffee seed extract (Coffea canephora) as anti-aging - Angga Saputra Yasir; Agesta Yesti Renita; Tutik Tutik (Pharmaciana, 2023)
Robusta coffee beans contain antioxidant compounds having anti-aging properties. This study aims to determine the content of secondary metabolites in robusta coffee bean extract, anti-aging effectiveness, and the best peel-off gel mask preparation concentration. The extraction method in this study used maceration with 96% ethanol as solvent. The extraction results were carried out by phytochemical screening and formulation of peel-off gel mask preparations, then tested for anti-aging effectiveness using 12 female volunteers and observed signs of aging, including pores, spots, wrinkles, and moisture for four weeks. Robusta coffee bean extraction results obtained a yield of 9.2%. The results of phytochemical screening showed that robusta coffee bean extract contains flavonoid compounds, alkaloids, tannins, and saponins. The results of the evaluation of the 0.5% formula of robusta coffee bean extract were the most preferred by volunteers. The best effectiveness and concentration test results were found in the peel-off gel mask preparation of 2% robusta coffee bean extract formula (F2) compared to blank and F1 (p-value <0.05). The percentage of improvement in the condition of the volunteers' skin, including pores, spots, wrinkles, and moisture, is 21.88 ± 4.22%, 21.57 ± 3.25%, 17.71 ± 2.44%, and 21.25 ± 3.62%, respectively.